Human Rights Violations in Indian Occupied Jammu and Kashmir: An Analysis of Indian Discriminatory Laws to Suppress the Independence Movement - Nayeem Maqbool Hurrah; Niyamatullah, (ASIAN Journal of International Peace & Security (AJIPS), 2022)
India is striving very hard to keep its control by using hard power tactics of committing human rights violations to suppress and oppress the independence movement in Indian Occupied Jammu and Kashmir (IOJK). The human rights violations range from mass killings, youth killings, torture, rapes, enforced disappearances and sexual abuses to political suppression. Lack of access to justice and impunity for human rights violations are major challenges for human rights in IOJK. The black laws enforced in IOJK such as Public Safety Act,(1978) and Armed Forces Special Powers Act,(1990)give unlimited powers to Indian Armed forces and have obstructed the normal course of law, impeded accountability and jeopardizedthe right to remedy for victims of human rights violations. Thousands of people have been killed, detained, injured and tortured since 1989. The study analyzed the gross human rights violations that took place in IOJK. The Research explored the methods which are being implemented and practiced to kill and curb the voices of people who have been fighting for their Right of self-determination.